2002
DOI: 10.1097/00042737-200206000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection and infertility

Abstract: H. pylori infection may increase the risk of developing reproductive disorders or worsen the clinical expression of this syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 25 publications
2
62
2
1
Order By: Relevance
“…Monoclonal antibodies raised against H. pylori antigens react with several different human tissues, including epithelial cells [46] and endothelial ones, as Franceschi et al [47] have described the existence of an antigenic mimicry between the vascular wall endothelium and H. pylori; some of us have shown a linear homology between human β-tubulin -largely diffused in the cytoskeleton of different cells -and H. pylori CagA, VacA and flagellar proteins [43]. It is therefore possible that the humoral immune response to certain H. pylori antigens may cross react with the vascular endothelial cells and inner ear antigens (such as P0-myelin and β-actin) -in addition to the cochlear ionic pumps -and damage the cochlear fine microstructure, leading to hearing impairment [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monoclonal antibodies raised against H. pylori antigens react with several different human tissues, including epithelial cells [46] and endothelial ones, as Franceschi et al [47] have described the existence of an antigenic mimicry between the vascular wall endothelium and H. pylori; some of us have shown a linear homology between human β-tubulin -largely diffused in the cytoskeleton of different cells -and H. pylori CagA, VacA and flagellar proteins [43]. It is therefore possible that the humoral immune response to certain H. pylori antigens may cross react with the vascular endothelial cells and inner ear antigens (such as P0-myelin and β-actin) -in addition to the cochlear ionic pumps -and damage the cochlear fine microstructure, leading to hearing impairment [45].…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmunity is often based on the phenomenon of molecular mimicry between human and bacterial antigens, and it is known that sharing epitopes can work like a trigger for certain autoimmune diseases. Some of us have recently discovered the existence of a linear homology between a main component of sperm flagellum, β-tubulin, and different antigens of H. pylori and have hypothesized that an immune cross reactivity may determine the association between H. pylori infection and male infertility [43].…”
Section: Introductionmentioning
confidence: 99%
“…For years, this organism has been known to cause only gastrointestinal pathology, but many studies have showed that H. pylori could be associated with several extra-gastric complications (5,23,24). The link between this organism and reproductive disorders has been also reported (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Among the study groups, 50% of the sperm samples and all follicular fluid samples were positive for H. pylori antibodies (24). Most of the previous studies used serological methods to evaluate the association between H. pylori and different consequences.…”
Section: Discussionmentioning
confidence: 99%
“…suggested to be an important cause of infertility [11,12]. We therefore propose to include the test for pathogenic strains of H. pylori when treating cases of infertility.…”
Section: Regardless Of the Mechanisms H Pylori Infection Has Beenmentioning
confidence: 99%